A self-report questionnaire for pregnancy-related symphyseal pain. (August 2020) - Flack, Natasha A.M.S.; Depledge, Jill; Hay-Smith, E. Jean C.; Stringer, Mark D.; Gray, Andrew R.; Woodley, Stephanie J.
Abstract: Background: Symphyseal pain (SP) experienced during pregnancy is a common condition that can negatively influence function and wellbeing. Despite its adverse impact on quality of life, standardised diagnostic criteria for SP as a distinct type of pelvic girdle pain (PGP) are lacking. Objectives: To develop a reliable self-administered instrument that could differentiate SP from posterior PGP in pregnant women, and ultimately be used for epidemiological or clinical purposes. Method: Qualitative data from 17 women (four focus groups) were used to develop a questionnaire. The questionnaire was tested against physical therapy diagnoses based on clinical assessment in 122 pregnant women with SP (n = 41), posterior PGP (n = 41) or no PGP (n = 40); 30 women repeated the questionnaire a day later to assess reliability. Multinomial logistic regression models were used to assess the performance of candidate items in distinguishing between the groups. Results/findings: The single questionnaire item relating to location of worst pain (diagrammatic form) is useful for differentiating SP from posterior PGP and individuals with no PGP. The worst pain location question with the addition of the Pelvic Girdle Questionnaire provides a measure of "SP with impact", and is the best combination for distinguishing SP and posterior PGP. Test-retest reliability scores were excellent. Conclusion: These findings provide new opportunities for diagnosing pregnancy-related SP, and highlight questionnaire items which best differentiate SP from posterior PGP. These items could be used in future epidemiological research, and in clinical settings as a quick, effective screening tool. Highlights: Women with SP reported higher pain intensity than those with posterior PGP. Women with SP had worse (higher) scores on the PGQ total score and activity scale. Worst pain location is useful for differentiating SP from posterior PGP and controls. Worst pain location combined with the PGQ proves a measure of "SP with impact".